Heterogeneous Authorship in Early Shakespeare and the Problem of Henry V. - MERRIAM, THOMAS (Literary & Linguistic Computing, 1998)
Several recent literary studies have proposed that Shakespeare was not the sole author of Titus Andronicus and the three Henry VI plays. This view is strengthened by a stylometric analysis which uses selected function words and letter frequencies that demonstrably differentiate Marlowe from Shakespeare. Both multilayer perceptrons and radial basis functions create a battery of tests which combine in a principal component analysis to give stable outcomes in testing complete works. The method is extended with twelve radial basis functions to attribute first acts of Shakespeare plays. The resulting bimodal pattern could indicate an admixture of Marlowe's (or Peel's) writing to Shakespeare's in several canonical first acts. Shakespeare may have re-written dramatic text first composed by other playwrights. The most unusual suggestion is that Shakespeare reworked a Marlowe original to create the first act of Henry V, with interpretive implications for an understanding of the play.